ANALISIS PSIKOLOGI SASTRA TERHADAP ASPEK KEPRIBADIAN TOKOH PADA NOVEL 7 SAYAP PENDOSA KARYA JIENARA - Elsyie Damayanti; Fera Zasrianita; Dina Putri Juni Astuti (Smart Education, 2026)
Abstract: This study is motivated by the importance of novels as a medium for characters to convey messages through writing. Novels are not only a medium for reading but also contain moral messages that authors wish to convey to readers. The main issue in this study is how authors describe psychological aspects of literature as reflected in the development of characters' personalities and what psychological factors influence changes in characters' personalities in Jienara's novel 7 Sayap Pendosa (Seven Wings of Sin). This novel presents the characters' complex inner conflicts due to life experiences, trauma, and social pressure. The approach used in this study is literary psychology with a qualitative descriptive method. The research data consists of narrative quotations and character dialogues in the novel that show aspects of the characters' personalities. Data collection techniques were carried out through reading and note-taking. The results of the study show that the characters' personalities are reflected through psychological aspects such as emotions, motivations, inner conflicts, and defense mechanisms. Factors that influence the characters' personalities include Id, Ego, Superego. The novel 7 Sayap Pendosa not only presents a fictional story, but also the psychology of characters that are realistic and relevant to social life. Keyword: Literary psychology, aspects of character personality, character personality factors, the novel